2002
DOI: 10.1038/nbt0302-256
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor antigen–specific induction of transcriptionally targeted retroviral vectors from chimeric immune receptor–modified T cells

Abstract: High-level systemic delivery of viral vectors to tumors has proved problematic as a result of immune neutralization, nonspecific adhesion, and clearance of circulating viral particles. Some cell types localize to tumors in response to particular biological properties associated with tumor growth. Their use to deliver viral vectors to tumors would allow precious viral stocks to be protected until they can be released at high local concentrations. Here, we describe a mechanism by which retroviral vector producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…injected viral particles. [16][17][18][19][20][21][22][23] Moreover, by associating virus with such T cells it may also be possible to ameliorate some the problems of virus neutralization, sequestration and nonspecific adhesion. 5 Indeed, we and others have shown that antigen-specific T cells can be used very effectively, in both immunecompetent and immune-deficient mice, to chaperone virus particles to tumors, to induce their local release at the tumor site and to promote increased therapy over and above the therapy induced by the cytolytic activity of the T cells alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…injected viral particles. [16][17][18][19][20][21][22][23] Moreover, by associating virus with such T cells it may also be possible to ameliorate some the problems of virus neutralization, sequestration and nonspecific adhesion. 5 Indeed, we and others have shown that antigen-specific T cells can be used very effectively, in both immunecompetent and immune-deficient mice, to chaperone virus particles to tumors, to induce their local release at the tumor site and to promote increased therapy over and above the therapy induced by the cytolytic activity of the T cells alone.…”
Section: Introductionmentioning
confidence: 99%
“…5 Indeed, we and others have shown that antigen-specific T cells can be used very effectively, in both immunecompetent and immune-deficient mice, to chaperone virus particles to tumors, to induce their local release at the tumor site and to promote increased therapy over and above the therapy induced by the cytolytic activity of the T cells alone. [16][17][18][19][20][21][22][23] In addition to T cells, several other types of cells have been used as carriers of genes/viruses to protect the virus from the multiple neutralizing and sequestering antiviral systems which the host normally uses to remove unwanted viral infections. [24][25][26][27] It is now clear that although the type of carrier and virus can differ it is possible to use cells to chaperone therapeutic viral particles to sites of tumor growth, either on, 21,23 or inside 16,17,24 the cells, and to generate potent antitumor therapy even in the presence of a fully intact immune system.…”
Section: Introductionmentioning
confidence: 99%
“…20 Various carriers have been evaluated and antigen-specific T cells have often been used. [24][25][26][27][28][29] Oncolytic viruses adsorbed onto lymphocytes are systemically delivered and released at the tumor site, a protease-rich environment; there, the oncolytic virus spreads and replicates in the tumor cells. 27,33,37 This strategy is called the 'hitchhiking method'.…”
Section: Antitumor Efficacy Of Herpes Simplex Virus a Kanzaki Et Almentioning
confidence: 99%
“…23 Various carriers have been evaluated, and antigen-specific T cells have often been used as a vector carrier. [24][25][26][27][28][29] Tumor antigenspecific T lymphocytes are a logical carrier for systemic virus delivery. 20,30 Moreover, tumor antigen-specific lymphocytes have been clearly shown to have inherent antitumor effects on their own.…”
Section: Introductionmentioning
confidence: 99%
“…In attempts to exploit the advantages offered by each of these virus vectors, several groups have constructed hybrids [1][2][3][4][5][6][7][8][9][10][11][12][13][14] that combine the high-titre and efficient transduction of adenoviruses with the stable transgene expression of the retroviral murine leukaemia virus (MLV). While this system induces long-term in vivo transgene expression, several natural characteristics of MLV may hinder its future clinical exploitation, not least the recent development of a leukaemia-like disease in two children following treatment with an MLV vector, which resulted in the suspension of the clinical trials.…”
Section: Introductionmentioning
confidence: 99%